Saint Lucia Workforce Development : SABER Country Report 2013 - World Bank Group (World Bank, Washington, DC, 2015)
Saint Lucia is a Small Island Developing State, whose economy suffered a significant setback after the devastation of its once solid banana industry in the early 2000s. The Island’s economy has also experienced anemic growth since the global financial crisis in 2008. The country is now highly dependent on tourism, the main source of employment and income, which makes up 39 percent of GDP approximately. As internal Consumption of commodities and industrial inputs also relies heavily on imports, Saint Lucia is vulnerable to external economic, political and climatic conditions. Over the last decade, the country has witnessed increased unemployment, especially within the youth bracket. In an economy with such limited diversification, unemployment has become structural. Understanding the threat that unemployment poses to the stability of the Island, the government has noted the urgency of developing strategies for providing relevant training and educational opportunities necessary to create a strong workforce.